Answer
To express each exponential function in the form \( 3^{k x} \), find the suitable constant \( k \) for each:
1. **First Set:**
- \( 4^{x} = 3^{\log_3 4 \cdot x} \) → \( k = \log_3 4 \)
- \( (\sqrt{3})^{x} = 3^{\frac{1}{2} x} \) → \( k = \frac{1}{2} \)
- \( \left(\frac{1}{9}\right)^{x} = 3^{-2x} \) → \( k = -2 \)
2. **Third Set:**
- \( 8^{\frac{2x}{3}} = 3^{2 \log_3 2 \cdot x} \) → \( k = 2 \log_3 2 \)
- \( 9^{\frac{3x}{2}} = 3^{3x} \) → \( k = 3 \)
- \( 16^{-\frac{3x}{4}} = 3^{-3 \log_3 2 \cdot x} \) → \( k = -3 \log_3 2 \)
3. **Fifth Set:**
- \( \left(\frac{1}{4}\right)^{2x} = 3^{-2 \log_3 4 \cdot x} \) → \( k = -2 \log_3 4 \)
- \( \left(\frac{1}{8}\right)^{-3x} = 3^{3 \log_3 8 \cdot x} \) → \( k = 3 \log_3 8 \)
- \( \left(\frac{1}{81}\right)^{\frac{x}{2}} = 3^{-2x} \) → \( k = -2 \)
**Summary:**
- For each exponential function, express it in the form \( 3^{k x} \) by finding the appropriate constant \( k \) based on the base of the original function.
Solution
It looks like you want to express each of the given exponential functions in the form \( 3^{k x} \) by finding the suitable constant \( k \). Let's analyze each expression one by one.
### 1. \( 4^{x}, \ (\sqrt{3})^{x}, \ \left(\frac{1}{9}\right)^{x} \)
#### a. \( 4^{x} \)
First, express 4 as a power of 3:
\[
4 = 3^{\log_3 4}
\]
So,
\[
4^{x} = \left(3^{\log_3 4}\right)^{x} = 3^{x \cdot \log_3 4}
\]
**Thus, \( k = \log_3 4 \).**
#### b. \( (\sqrt{3})^{x} \)
\[
\sqrt{3} = 3^{1/2}
\]
So,
\[
(\sqrt{3})^{x} = \left(3^{1/2}\right)^{x} = 3^{(1/2) x}
\]
**Thus, \( k = \frac{1}{2} \).**
#### c. \( \left(\frac{1}{9}\right)^{x} \)
\[
\frac{1}{9} = 9^{-1} = (3^{2})^{-1} = 3^{-2}
\]
So,
\[
\left(\frac{1}{9}\right)^{x} = \left(3^{-2}\right)^{x} = 3^{-2x}
\]
**Thus, \( k = -2 \).**
### 3. \( 8^{\frac{2x}{3}}, \ 9^{\frac{3x}{2}}, \ 16^{-\frac{3x}{4}} \)
#### a. \( 8^{\frac{2x}{3}} \)
\[
8 = 2^{3} = \left(3^{\log_3 2}\right)^{3} = 3^{3 \log_3 2}
\]
So,
\[
8^{\frac{2x}{3}} = \left(3^{3 \log_3 2}\right)^{\frac{2x}{3}} = 3^{2x \cdot \log_3 2}
\]
**Thus, \( k = 2 \log_3 2 \).**
#### b. \( 9^{\frac{3x}{2}} \)
\[
9 = 3^{2}
\]
So,
\[
9^{\frac{3x}{2}} = \left(3^{2}\right)^{\frac{3x}{2}} = 3^{3x}
\]
**Thus, \( k = 3 \).**
#### c. \( 16^{-\frac{3x}{4}} \)
\[
16 = 2^{4} = \left(3^{\log_3 2}\right)^{4} = 3^{4 \log_3 2}
\]
So,
\[
16^{-\frac{3x}{4}} = \left(3^{4 \log_3 2}\right)^{-\frac{3x}{4}} = 3^{-3x \cdot \log_3 2}
\]
**Thus, \( k = -3 \log_3 2 \).**
### 5. \( \left(\frac{1}{4}\right)^{2x}, \ \left(\frac{1}{8}\right)^{-3x}, \ \left(\frac{1}{81}\right)^{\frac{x}{2}} \)
#### a. \( \left(\frac{1}{4}\right)^{2x} \)
\[
\frac{1}{4} = 4^{-1} = \left(3^{\log_3 4}\right)^{-1} = 3^{-\log_3 4}
\]
So,
\[
\left(\frac{1}{4}\right)^{2x} = \left(3^{-\log_3 4}\right)^{2x} = 3^{-2x \cdot \log_3 4}
\]
**Thus, \( k = -2 \log_3 4 \).**
#### b. \( \left(\frac{1}{8}\right)^{-3x} \)
\[
\frac{1}{8} = 8^{-1} = \left(3^{\log_3 8}\right)^{-1} = 3^{-\log_3 8}
\]
So,
\[
\left(\frac{1}{8}\right)^{-3x} = \left(3^{-\log_3 8}\right)^{-3x} = 3^{3x \cdot \log_3 8}
\]
**Thus, \( k = 3 \log_3 8 \).**
#### c. \( \left(\frac{1}{81}\right)^{\frac{x}{2}} \)
\[
\frac{1}{81} = 81^{-1} = \left(3^{4}\right)^{-1} = 3^{-4}
\]
So,
\[
\left(\frac{1}{81}\right)^{\frac{x}{2}} = \left(3^{-4}\right)^{\frac{x}{2}} = 3^{-2x}
\]
**Thus, \( k = -2 \).**
---
### Summary of Constants \( k \)
1. **First Set:**
- \( 4^{x} = 3^{(\log_3 4) x} \) → \( k = \log_3 4 \)
- \( (\sqrt{3})^{x} = 3^{\frac{1}{2} x} \) → \( k = \frac{1}{2} \)
- \( \left(\frac{1}{9}\right)^{x} = 3^{-2x} \) → \( k = -2 \)
3. **Third Set:**
- \( 8^{\frac{2x}{3}} = 3^{2 (\log_3 2) x} \) → \( k = 2 \log_3 2 \)
- \( 9^{\frac{3x}{2}} = 3^{3x} \) → \( k = 3 \)
- \( 16^{-\frac{3x}{4}} = 3^{-3 (\log_3 2) x} \) → \( k = -3 \log_3 2 \)
5. **Fifth Set:**
- \( \left(\frac{1}{4}\right)^{2x} = 3^{-2 (\log_3 4) x} \) → \( k = -2 \log_3 4 \)
- \( \left(\frac{1}{8}\right)^{-3x} = 3^{3 (\log_3 8) x} \) → \( k = 3 \log_3 8 \)
- \( \left(\frac{1}{81}\right)^{\frac{x}{2}} = 3^{-2x} \) → \( k = -2 \)
---
**Note:** \( \log_3 a \) represents the logarithm of \( a \) with base 3. Depending on the context or the specific requirements of your problem, you might need to simplify these logarithmic expressions further or leave them as is.
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution